Comparative Analysis of Gut Microbiota Between Healthy and Diarrheic Horses - Li, Yaonan; Lan, Yanfang; Zhang, Shuang; Wang, Xiaoli (Frontiers in Veterinary Science, 2022)
Increasing evidence reveals the importance of gut microbiota in animals for regulating intestinal homeostasis, metabolism and host health. Gut microbial communities have been reported to be closely related to many diseases, but information regarding diarrheic influence on gut microbiota in horses remains scarce. Therefore, this study investigated and compared gut microbial changes in horses during diarrhea. Results showed that the alpha diversity of gut microbiota in diarrheic horses decreased observably, accompanied by obvious shifts in taxonomic compositions. The dominant bacterial phyla (Firmicutes, Bacteroidetes, Spirochaetes and Kiritimatiellaeota) and genera (uncultured_bacterium_f_Lachnospiraceae, uncultured_bacterium_f_p-251-o5, Lachnospiraceae_AC2044_group and Treponema_2) in healthy and diarrheic horses were same regardless of health status but different in abundances. Compared with healthy horses, the relative abundances of Planctomycetes, Tenericutes, Firmicutes, Patescibacteria and Proteobacteria in the diarrheic horses were observably decreased, whereas Bacteroidetes, Verrucomicrobia and Fibrobacteres were dramatically increased. Moreover, diarrhea also resulted in a significant reduction in the proportion of 31 genera and a significant increase in the proportion of 14 genera. Taken together, the current study demonstrated that gut bacterial diversity and abundance of horses changed significantly during diarrhea. Additionally, these findings also demonstrated that the dysbiosis of gut microbiota may be an important driving factor of diarrhea in horses.